Short DNA containing χ sites enhances DNA stability and gene expression in E. coli cell‐free transcription–translation systems. Issue 9 (23rd May 2017) - Marshall, Ryan; Maxwell, Colin S.; Collins, Scott P.; Beisel, Chase L.; Noireaux, Vincent
ABSTRACT: Escherichia coli cell‐free transcription–translation (TXTL) systems offer versatile platforms for advanced biomanufacturing and for prototyping synthetic biological parts and devices. Production and testing could be accelerated with the use of linear DNA, which can be rapidly and cheaply synthesized. However, linear DNA is efficiently degraded in TXTL preparations from E. coli . Here, we show that double‐stranded DNA encoding χ sites—eight base‐pair sequences preferentially bound by the RecBCD recombination machinery—stabilizes linear DNA and greatly enhances the TXTL‐based expression and activity of a fluorescent reporter gene, simple regulatory cascades, and T7 bacteriophage particles. The χ‐site DNA and the DNA‐binding λ protein Gam yielded similar enhancements, and DNA with as few as four χ sites was sufficient to ensure robust gene expression in TXTL. Given the affordability and scalability of producing the short χ‐site DNA, this generalized strategy is expected to advance the broad use of TXTL systems across its many applications. Biotechnol. Bioeng. 2017;114: 2137–2141. © 2017 Wiley Periodicals, Inc. Abstract : A short, dsDNA containing χ sites, recognized by the RecBCD recombination machinery, offers a simple and affordable means of stabilizing linear DNA and greatly enhancing gene expression in E. coli extract‐based cell‐free systems. This method is easy to use, applicable to most of the current available TXTL systems, and generalizable to new TXTL platforms, in particular those developed for biomanufacturing and prototyping synthetic biology constructs and circuits.